Implementasi Teknologi Mekatronika Berbasis ESP32 untuk Otomatisasi Penyiraman Tanaman pada Sistem Pertanian Cerdas - Aroihan Khozinatul Asror; Panji Romadon; Luis Desta Vianus (Jurnal Studi Multidisiplin Qomaruna, 2026)
The advancement of Internet of Things (IoT) technology has created significant opportunities to improve resource management efficiency in the agricultural sector, particularly in automated irrigation systems. This study aimed to design and evaluate an automatic plant irrigation system based on the ESP32 microcontroller capable of monitoring and controlling environmental conditions in real time. An engineering experimental approach was employed, including literature review, hardware and software design, system integration, performance testing, and data analysis. The developed system consists of an ESP32 microcontroller, a YL-69 soil moisture sensor, a DHT22 temperature and humidity sensor, a relay module, and a direct current (DC) water pump. Remote monitoring and control were implemented through Blynk and Telegram applications using WiFi connectivity. System testing was conducted under various soil moisture conditions to assess sensor accuracy, automation responsiveness, and communication stability. The results indicate that the system operated automatically according to predefined soil moisture thresholds, achieving sensor accuracy above 90%. Furthermore, water use efficiency improved by 25–30% compared to manual irrigation methods. The system successfully transmitted real-time data with an average delay of less than three seconds. These findings demonstrate that the implementation of an IoT-based automatic irrigation system has strong potential to support smart farming practices that are more efficient, cost-effective, and sustainable, particularly for household-scale, greenhouse, and urban agriculture applications.